IL-36α suppresses proliferation of ovarian cancer cells - Lei Chang; Ruixia Guo; Zhongfu Yuan (Tumor Biology)
Interleukin-36α (IL-36α), also formerly known as IL-1F6, is pertaining to IL-1 family members that has been shown to play an important pro-inflammatory role in chronic immune disorders. However, the role IL-36α in the setting of cancer remains unknown. Here, in our study, to investigate the clinical relevance of IL-36α in ovarian cancer, clinicopathological significance as well as expression level of IL-36α were analyzed in epithelial ovarian cancer clinical tissues and paired normal control. To explore the biological role of IL-36α in vitro in epithelial ovarian cancer cells, both overexpression and knockdown of IL-36α were performed. Based on the successful re-expression and silencing of IL-36α, proliferation, migration, and invasion were evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, wound-healing, and Transwell assays, respectively. To further confirm the effect over proliferation in vivo, nude mice xenografted with epithelial ovarian cancer cells whose endogenous IL-36α was stably upregulated or downregulated were employed. It was found that IL-36α was shown to be markedly downregulated in epithelial ovarian cancer tissues relative to paired normal control and that reduced IL-36α expression was significantly associated with poor overall prognosis. In addition, IL-36α was observed to be able to suppress the growth of epithelial ovarian cancer cells both in vivo and in vitro. Taken together, IL-36α was displayed to be able to suppress the growth of epithelial ovarian cancer cells in our setting, which is suggestive of its druggable potential in curing the epithelial ovarian cancer and that upregulation of IL-36α was found to be capable of inhibiting the growth of epithelial ovarian cancer cells.